2007
DOI: 10.1210/jc.2007-0092
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygosity for a Mutation in the Growth Hormone-Releasing Hormone Receptor Gene Does Not Influence Adult Stature, But Affects Body Composition

Abstract: Context: Biallelic mutations in the GHRH receptor (GHRHR) gene (GHRHR) are a frequent cause of isolated GH deficiency (IGHD).Although heterozygous carriers of these mutations appear normal, we hypothesized that heterozygosity for a GHRHR mutation might be associated with a subclinical phenotype. Methods:We studied members of a large Brazilian kindred with IGHD (Itabaianinha cohort) caused by a homozygous null GHRHR mutation. We compared 76 adult subjects (age, 25-75 yr) heterozygous for the mutation (WT/MT) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…Different from the homozygous affected young adults, who exhibit severe short stature, with decreased FFM (kg) and increased percent of FM (45), young adult subjects HTZ for the Itabaianinha GHRHR mutation show no significant difference in height, but have lower FFM, no difference in the percent of FM and a trend of reduction in FM, when compared with homozygous normal controls from the same kindred (78). We hypothesized that a partial reduction in GH secretion might cause these changes in body composition, without affecting height.…”
Section: Heterozygous (Htz) Phenotypementioning
confidence: 99%
See 1 more Smart Citation
“…Different from the homozygous affected young adults, who exhibit severe short stature, with decreased FFM (kg) and increased percent of FM (45), young adult subjects HTZ for the Itabaianinha GHRHR mutation show no significant difference in height, but have lower FFM, no difference in the percent of FM and a trend of reduction in FM, when compared with homozygous normal controls from the same kindred (78). We hypothesized that a partial reduction in GH secretion might cause these changes in body composition, without affecting height.…”
Section: Heterozygous (Htz) Phenotypementioning
confidence: 99%
“…These features have been published in 42 different publications (2,19,22,25,27,29,30,31,32,33,36,37,38,40,41,44,45,46,47,48,49,50,51,52,53,54,56,57,61,62,63,64,66,67,68,74,75,76,77,78,79,80). We have used this experiment of nature to discover 'usual laws of nature' as suggested by William Harvey, and to understand some aspects of more common conditions such as short stature, insulin resistance, diabetes, atherosclerosis, osteoporosis, cancer and ultimately longevity.…”
Section: Introductionmentioning
confidence: 99%
“…A genetic association study has shown that heterozygosity for a GHRHR mutation is associated with changes in body composition and possibly an increase in insulin sensitivity. 22 Glutamate dehydrogenase 1 is involved in glutamate catabolism. The activated glutamate dehydrogenase enhances oxidation of glutamate and, in turn, increases the regulation of insulin secretion.…”
Section: Metabolic Mechanism Genesmentioning
confidence: 99%
“…20 The possibility of a milder phenotype in heterozygous carriers of a GHRHR mutation has only been suggested recently. 15 In that early work we had not detected an effect on adult stature. That population was, however, composed mostly by young adults.…”
Section: Discussionmentioning
confidence: 83%
“…14 In a previous study of the Itabaianinha kindred, we have shown that adult MUT/N subjects have reduced weight, body mass index (BMI) and MM when compared with homozygous normal (N/N) subjects, but their adult stature is not significantly reduced. 15 However, only 10% of those individuals were ⩾ 60 years of age. We hypothesized that the height reduction may manifest itself during senescence.…”
Section: Introductionmentioning
confidence: 99%